Banana Transcription Factor MaERF11 Recruits Histone Deacetylase MaHDA1 and Represses the Expression of MaACO1 and Expansins during Fruit Ripening . Issue 2 (5th April 2016) - Han, Yan-Chao; Kuang, Jian-Fei; Chen, Jian-Ye; Liu, Xun-Cheng; Xiao, Yun-Yi; Fu, Chang-Chun; Wang, Jun-Ning; Wu, Ke-Qiang; Lu, Wang-Jin
Abstract : ETHYLENE RESPONSE FACTOR11 (MaERF11) and HDA1 interact to repress the expression of ACO1 and expansins via histone deacetylation. Abstract: Phytohormone ethylene controls diverse developmental and physiological processes such as fruit ripening via modulation of ethylene signaling pathway. Our previous study identified that ETHYLENE RESPONSE FACTOR11 (MaERF11), a transcription factor in the ethylene signaling pathway, negatively regulates the ripening of banana, but the mechanism for the MaERF11-mediated transcriptional regulation remains largely unknown. Here we showed that MaERF11 has intrinsic transcriptional repression activity in planta. Electrophoretic mobility shift assay and chromatin immunoprecipitation analyses demonstrated that MaERF11 binds to promoters of three ripening-related Expansin genes, MaEXP2, MaEXP7 and MaEXP8, as well as an ethylene biosynthetic gene MaACO1, via the GCC-box motif. Furthermore, expression patterns of MaACO1, MaEXP2, MaEXP7, and MaEXP8 genes are correlated with the changes of histone H3 and H4 acetylation level during fruit ripening. Moreover, we found that MaERF11 physically interacts with a histone deacetylase, MaHDA1, which has histone deacetylase activity, and the interaction significantly strengthens the MaERF11-mediated transcriptional repression of MaACO1 and Expansins . Taken together, these findings suggest that MaERF11 may recruit MaHDA1 to its target genes and repress their expression via histone deacetylation.